When Rules Turn Loose: An Analysis of the Concept of Rules and Exceptions - Agpaoa, Jerwin F. (Social Science Diliman: A Philippine Journal of Society and Change, 2013)
This paper seeks to clarify the notion of rules and exceptions and how they influence human behavior. Human beings, as Aristotle claims, are socio-political animals, and their existence is generally defined by how they associate with each other in society. The values one develops are related to the regulation of societal action. It is possible, however, that there are multifaceted valuations within the same society and that different rules may be created to account for them. These rules may fail to account for all the values that exist in society. More so, these rules may either be modified or changed over time to address society’s evolution. Given the dynamism, individuals may bargain for the creation of exceptions to rules that define their existence as importantly as rules do. Keywords: Rules, exceptions, deliberation, equality, meritorious/special case, equity, justice